Gender in Jobs Diagnostics : A Guidance Note - Scarpari, Raquel (World Bank, Washington, DC, 2020)
The WBG's Jobs Group has developed a standardized Jobs Diagnostics tool to help countries identify key challenges in the effort to create jobs, improve the quality of jobs, and provide access to jobs. One important dimension of a good jobs diagnosis is to uncover gender disparities in labor market outcomes and understand the underlying factors that cause those disparities. The Jobs Diagnostic tool enables the user to identify priority jobs-relevant gender challenges through the production of an extensive set of sex-disaggregated indicators and regression analyses, employing standardized household and enterprise data. Underlying constraints can be further explored, through complementary in-depth analysis of country-specific quantitative and qualitative information.